Vitamin C content in orange juices obtained by different methods - Kujawińska, Maria; Kawulok, Izabela; Szczyrba, Anna; Grot, Martina; Bielaszka, Agnieszka; Nieć-Leśniak, Joanna; Grajek, Mateusz (Journal of Education, Health and Sport, 2022)
Introduction Proper nutrition has the task of providing the right amount of energy and nutrients. A balanced diet should include vegetables and fruit at every meal. These products are rich in vitamin C, which is involved in many metabolic pathways in the body. A well-balanced diet will generally provide you with enough ascorbic acid. The content of vitamins in products depends on many factors, including the place of origin of the product, season, species, processing methods, or the conditions and time of storage. Vitamin C is easily destroyed by contact with oxygen, light radiation or metal ions. Aim of the study The aim of the study is to assess the content of vitamin C in juices squeezed from different types of oranges using various processing methods. Material and methods Three species of oranges were used for the study: Valencia, Saluciana and Novelina. Each type of orange was squeezed with 3 processing methods, using: a juicer, a slow-speed squeezer and a manual squeezer. The determination of vitamin C content in the obtained juices was performed by the Tillmans titration method with the use of standard, blue, 2,6-dichlorophenolindophenol dye. The vitamin C content in juices was determined: immediately after squeezing the juice, one hour after squeezing and 24 hours after squeezing. The juices were stored in the refrigerator between determinations. A pH meter was used to measure the pH, and a portable digital sucrose refractometer was used for the% sucrose measurement. Results The highest content of vitamin C immediately after pressing was observed in the juice of hand-squeezed oranges from the Salustiana variety. The decrease in vitamin C after 24 hours averaged 37.8%. Statistically significant differences were found between the method of squeezing and the time after squeezing the juice. Valencia variety was characterized by the highest pH, Navelina - the lowest. Significant differences were found in the mean level of the pH indicator and the type of orange.